Science club and school laboratory: Teachers’ perceptions in science teaching in the early years of elementary education (Revista Contexto & Educação, 2026)
In the face of the growth of anti-scientific discourses and misinformation on social networks, it is essential to strengthen educational strategies that promote Scientific Literacy (CA). The idea of implementing a Science Club aims to create opportunities for investigative learning, arouse students' interest in Science and encourage the development of a critical attitude. To validate this proposal, the perceptions of teachers in the early years about the use of the laboratory and the Science Club were investigated. Through the analysis of the questionnaire applied, the main obstacles faced and the interest of teachers in the adoption of investigative methodologies were identified. The results reveal that, despite the recognition of the importance of experimentation, factors such as lack of time, specific training and physical structure limit its realization. On the other hand, there is broad acceptance of the proposal as a strategy to promote CA. It is concluded that initiatives like this are essential to qualify the teaching of Science in the early years.
Keywords: science teaching; scientific literacy; school laboratory; science club; teacher training